A good man is hard to find : and other stories - O'Connor, Flannery (Mariner Books, Houghton Mifflin Harcourt, 2019)
The collection that established O'Connor's reputation as one of the American masters of the short story. The volume contains the celebrated title story, a tale of the murderous fugitive The Misfit, as well as "The Displaced Person" and eight other stories.